The influence of financial literacy, perceptions of gold prices and pocket money on interest in gold investment (Survey of UIS Malaysia students and STIE Sutaatmadja Subang students) - Fauzyah, Ninda Juliana; Kurniawan, Asep; Agnyoto, Panji; Ab Hadi, Siti Hajar Bt (Proceeding International Conference on Accounting and Finance, 2024)
One of the topics that is often discussed in the world is the growth of the global economy and finance, this is influenced by globalization. This economic growth is a reason for people to think ahead about how to keep up with the flow and pace of the economy. One way to overcome this is by investing, one of which is investing in gold. The aim of this research is to determine the influence of financial literacy, perceptions of gold prices, and pocket money on interest in investing in gold among UIS Malaysia students and STIE Sutaatmadja Subang students. The population used in this research were UIS Malaysia students and STIE Sutaatmadja Subang students. The analysis technique uses multiple linear regression analysis. The results of this research show that financial literacy, perspective on gold prices, and pocket money have a positive and significant effect on interest in investing in gold among UIS Malaysia students and STIE Sutaatmadja Subang students.